Angioleiomyoma of the uterus presenting as an endometrial polyp: An uncommon occurrence of two cases with a literature review - Vamsi K. Kapaganti; Mohammed Shahin; Anurag Mishra; Pruthiviraj Sethi; Saubhagya K. Jena; Bhismadev Chhatria; Pavithra Ayyanar (Indian Journal of Pathology and Microbiology)
Angioleiomyoma is a benign neoplasm that arises from vascular smooth muscle cells. Angioleiomyoma of the endometrium is very uncommon. The differential diagnoses of this entity are myopericytoma, angiomyofibroblastoma, endometrial stromal tumor, and perivascular epithelioid cell tumor. 31-year-old and 45-year-old patients presented with heavy menstrual bleeding, lower abdomen pain, and dysmenorrhea. Perspeculum and radiological investigations showed an endometrial polyp. They underwent diagnostic hysteroscopy, polypectomy, and endometrial biopsy. Polypectomy specimens of both cases revealed polypoidal lesions lined by the endometrium. The core of the polyp was arranged in long intersecting bundles of spindle cells and interconnecting anastomotic patterns with many intervening thick-walled blood vessels. These spindle cells have oval and cigar-shaped nuclei, fine chromatin, and a moderate amount of eosinophilic cytoplasm, resembling smooth muscle cells. These smooth muscle cells of the vessel wall were merging with the adjacent walls of the blood vessel. There was no nuclear atypia or necrosis. The mitotic rate was 0–1/10 HPF. Focal areas of hyalinization and adipocytic components were noted in one case. The endometrial glands did not show intraepithelial or invasive neoplasia. On immunohistochemistry (IHC), these spindle cells were diffuse and strongly immunopositive for SMA and Desmin. CD34 highlighted the endothelial lining of the prominent thick-walled blood vessels. By correlating with histomorphology and IHC positivity, a diagnosis of angioleiomyomatous polyp of endometrium was rendered. We report two uncommon cases of angioleiomyoma of the endometrium and discuss the differential diagnosis and literature review.